Analisis Produktivitas Tenaga Kerja Terhadap Hasil Produksi Di PT. Exedy Manufacturing Indonesia Sirnabaya Karawang - Attie Komala Dewi; Wike Pertiwi (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Production management is the activity of planning, organizing, directing, and monitoring the efforts of the members of the organization and use of resources of other organizations in order to achieve organizational goals that have been set. Inthis activity, important for the department planning product and inventory control to play a role in the management of production in creating a product planning as well as play a role in the control of inventory. In the lecture field work, the students who participated in the lecture field work in a Pie PT Hai International Wiratama can learn about production management, in particular the role of the department planning production and inventory control inmaintaining the production process in accordance with the obligations ditentkanbased on the rules. From the results of observation and interview in the activities of the working class of this field can be seen that the product planning and inventory control in charge of keeping the stability of raw material, semi-finished materials, as well as the state and the number of finished products ready to be marketed.